(9/x) (x) ^ (1-9/x)
2006-11-16 09:54:03
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
y = x ^ 9/x
y ' = ?
Solution: ln y = (9/x) (ln x)
y '/y = (9/x)' (ln x) + (ln x)' (9/x)
" = ((9)' (x) - (x)' (9))/x^2 (ln x) + (ln x)' (9/x)
" = -9 /x^2 (ln x) + (1/x) (9/x)
" = (-9 ln x)/x^2 + (9/x^2)
" = (-9 ln x + 9)/x^2
y '/y = (-9 ln x + 9)/x^2
y ' = x ^ 9/x (-9 ln x + 9)/x^2
y ' = 9x ^ 9/x (-ln x + 1)/x^2
Answer => y ' = 9x ^ 9/x ( 1 - ln x)/x^2
2006-11-16 10:17:41
·
answer #2
·
answered by frank 7
·
0⤊
0⤋
i honestly like them. It facilitates me get into "more recent" bands, which I have a problematic time doing. maximum of those more recent bands having an "older" sound is as a results of the actual shown actuality that they are only putting their musical idea into *their* music. it is not a large deal, if some thing, it is honestly fairly cool. ie: many human beings say Oasis is and are a Beatles' knock-off, yet I disagree. they have many similarities, yet they are diverse. That replaced into only one in all their well-liked bands. I dig that. same w/ Lenny Kravitz and Jimi Hendrix, Wolfmother and Led Zeppelin/Black Sabbath. Edit; constructive, i will verify a number of that out. i have honestly heard lots of stuff about Badfinger, specially round right here, yet not in any respect honestly heard them. i does not concepts in case you e-mailed me some songs. :D
2016-11-24 23:09:37
·
answer #3
·
answered by sheryl 4
·
0⤊
0⤋
just do this first...
ln y = 9/x * ln x
then differentiate both side. Implicit Differentiation.
2006-11-16 09:53:55
·
answer #4
·
answered by Sora Aoi 2
·
0⤊
0⤋
y = x^(9/x)
= e^[(9lnx)/x] (since x = e^(lnx)
= e^u where u = 9lnx/x Thus du/dx = 9(1/x² - lnx)/x² by quotient rule
ie du/dx = 9(1 - x²lnx)/x^4
So dy/dx = dy/du * du/dx
= e^u * 9(1/x² - lnx)/x²
= 9(1 - x²lnx) / x^4 * x^(9/x)
= 9(1 - x²lnx)x^(9/x - 4)
= 9(1 - x²lnx)x^[(9 - 4x)/x]
PS Made some modifications on perusing ... sign and transcription errors .... sorry!!!
2006-11-16 09:57:17
·
answer #5
·
answered by Wal C 6
·
0⤊
0⤋
y = x^(9x^-1)
Take the ln of both sides
ln(y) = (9x^-1)ln(x)
Differentiate implicitly wrt x
1/y* dy/dx = -9x^-2*ln(x) + (9x^-1)*x^-1
dy/dx = y(-9)x^(-2)(1+ln(x))
2006-11-16 10:29:51
·
answer #6
·
answered by ve1luv 2
·
0⤊
0⤋
take log on both sides
log y=9/x log x
xlogy=9logx
derivating wrt x
log y+x/y dy/dx =9/x
dy/dx=y/x(9/x-log y)
2006-11-16 09:54:21
·
answer #7
·
answered by . 3
·
0⤊
0⤋
y'=(-9*(9/x)*x^(9/x-1))/x^2
or
lny=(9lnx)*x^-1
y'/y=9/x^2-(9lnx)/x^2
y'=y(9-9lnx)/x^2
yeah i think the natural log is easier
2006-11-16 09:53:22
·
answer #8
·
answered by rawfulcopter adfl;kasdjfl;kasdjf 3
·
0⤊
0⤋